2022
DOI: 10.3390/cells11030337
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Usefulness of Human Adipose-Derived Stem Cell Spheroids Formed Using SphereRing® and the Lethal Damage Sensitivity to Synovial Fluid In Vitro

Abstract: Osteoarthritis (OA) is an irreversible degenerative condition causing bone deformation in the joints and articular cartilage degeneration with chronic pain and impaired movement. Adipose-derived stem cell (ADSC) or crushed adipose tissue injection into the joint cavity reportedly improve knee function and symptoms, including pain. Stem cell spheroids may be promising treatment options due to their anti-inflammatory and enhanced tissue regeneration/repair effects. Herein, to form human ADSC spheroids, we used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…On the other hand, ADSCs possess a high immunoregulatory capacity as a result of their secretion of immunomodulatory and growth factors [ 39 ]. In a previous study, we generated ADSC spheroids using a specialized culture device and demonstrated an increased secretion of the representative anti-inflammatory cytokine IL-10 compared with 2D cultures [ 28 ]. IL-10 has inhibitory effects on intra-articular inflammation in patients with knee OA [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, ADSCs possess a high immunoregulatory capacity as a result of their secretion of immunomodulatory and growth factors [ 39 ]. In a previous study, we generated ADSC spheroids using a specialized culture device and demonstrated an increased secretion of the representative anti-inflammatory cytokine IL-10 compared with 2D cultures [ 28 ]. IL-10 has inhibitory effects on intra-articular inflammation in patients with knee OA [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 ). Cytokine secretion by ADSCs is influenced by variations in the culture environment, with hypoxic conditions and spheroid cultures promoting IL-10 secretion by ADSCs [ 28 , 40 , 42 ]. Therefore, it is suggested that stirred culture with AMS-adherent ADSCs may also impact the ability of ADSCs to secrete IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study illustrated the stimulatory impact of spheroid formation on ASCs towards endothelial lineage by observing increased expression of cluster of differentiation (CD) 31, which persisted following the seeding of ASC spheroids on cell sheets. Furthermore, compared to ASC sheets, ASC spheroid sheets exhibited heightened expression of VEGF and HGF, and the conditioned medium from ASC spheroid sheets significantly promoted tube formation of endothelial cells in vitro (136).…”
Section: Paracrine Secretionmentioning
confidence: 93%